Amyloid deposition at the carotid artery in an ATTRwt amyloidosis patient: a case report. Issue 12 (17th December 2022) - Ozaki, Hirokazu; Mitsui, Nobuyuki; Kinoshita, Manabu; Tanino, Mishie; Kimura, Teruo
Abstract: Systemic amyloidosis is a diseased condition where misfolded proteins deposit in various organs in the form of amyloids, and transthyretin deposition, termed ATTR amyloidosis, can be either an age-related amyloid formation from misfolded wild-type TTR (ATTRwt) or by hereditary TTR malfunction due to mutation in the TTR gene (ATTRv). Although ATTRwt amyloidosis can cause various diseases, such as cardiac failure, conduction disturbances, arrhythmias and carpal tunnel syndrome, it is still under-recognised considering its clinical significance. Here the authors report a case of ATTRwt amyloidosis leading to carotid stenosis requiring surgical intervention. To the best of our knowledge, the current report is the first that described histopathological evidence of amyloid deposition in the carotid artery due to ATTRwt amyloidosis.